Cutaneous B-Cell Pseudolymphoma Successfully Treated with Triamcinolone Acetonide - Anggraeni, Tulus Dyah; Nurdin, Airin; Tabri, Farida; Ilyas, Faridha (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Cutaneous pseudolymphoma (PSL) is a reactive polyclonal benign lymphoproliferative process in the skin that simulate cutaneous lymphomas clinically, histologically, or both, predominantly composed of either B-cells or T-cells, localized or disseminated. PSL clinically manifests as solitary nodules or plaque on the face. In cases where cutaneous PSL is suspected, the most crucial part is diagnosis, to differentiate benign or malignant lesion. Diagnosis required a combination of clinical, histopathological, and immunohistochemistry examination. CASE REPORT: A 59-year-old man presented with asymptomatic erythematous plaque on her cheek for 6 months before. Histopathological examination revealed dense small lymphocytic infiltration forming lymphoid follicles with centrum germinativum that partially destructed skin appendice glands. Immunohistochemistry examination showed positive result on cluster of differentiation (CD)20 and CD3 staining. With domination of CD20 treatment: Patient was treated with intralesional injection of triamcinolone acetonide 10 mg/ml and showed satisfying result after 3 times injection. CONCLUSION: A cutaneous B-cell PSL in a 59-year-old man was diagnosed based on history and physical, histopathological, and also immunohistochemistry examination. Intralesional injection of 10 mg/ml triamcinolone acetonide gave satisfying result.